Genetic delivery of an immunoRNase by an oncolytic adenovirus enhances anticancer activity. Issue 9 (12th November 2014) - Fernández‐Ulibarri, Inés; Hammer, Katharina; Arndt, Michaela A.E.; Kaufmann, Johanna K.; Dorer, Dominik; Engelhardt, Sarah; Kontermann, Roland E.; Hess, Jochen; Allgayer, Heike; Krauss, Jürgen; Nettelbeck, Dirk M.
<x xml:space="preserve">Abstract</x> Antibody therapy of solid cancers is well established, but suffers from unsatisfactory tumor penetration of large immunoglobulins or from low serum retention of antibody fragments. Oncolytic viruses are in advanced clinical development showing excellent safety, but suboptimal potency due to limited virus spread within tumors. Here, by developing an immunoRNase‐encoding oncolytic adenovirus, we combine viral oncolysis with intratumoral genetic delivery of a small antibody‐fusion protein for targeted bystander killing of tumor cells (viro‐antibody therapy). Specifically, we explore genetic delivery of a small immunoRNase consisting of an EGFR‐binding scFv antibody fragment fused to the RNase Onconase (ONCEGFR) that induces tumor cell death by RNA degradation after cellular internalization. Onconase is a frog RNase that combines lack of immunogenicity and excellent safety in patients with high tumor killing potency due to its resistance to the human cytosolic RNase inhibitor. We show that ONCEGFR expression by oncolytic adenoviruses is feasible with an optimized, replication‐dependent gene expression strategy. Virus‐encoded ONCEGFR induces potent and EGFR‐dependent bystander killing of tumor cells. Importantly, the ONCEGFR‐encoding oncolytic adenovirus showed dramatically increased cytotoxicity specifically to EGFR‐positive tumor cells in vitro and significantly enhanced therapeutic activity in a mouse xenograft tumor model. The latter demonstrates that ONCEGFR is expressed at levels sufficient to trigger tumor cell killing in vivo. The established ONCEGFR‐encoding oncolytic adenovirus represents a novel agent for treatment of EGFR‐positive tumors. This viro‐antibody therapy platform can be further developed for targeted/personalized cancer therapy by exploiting antibody diversity to target further established or emerging tumor markers or combinations thereof.